Endovascular treatment of penetrating nail gun injury of the cervical spine and vertebral artery: a case report - Alexei Christodoulides; Scott Mitchell; Bradley N. Bohnstedt (Journal of Trauma and Injury)
In this report, we present a case of high cervical penetrating trauma with vertebral artery injury and outline preprocedural, procedural, and postprocedural considerations with recommendations for the treatment of similar injuries. Management involves multiple imaging modalities, including X-ray imaging, computed tomography, computed tomography angiography, magnetic resonance imaging, and catheter angiography. We recommend endovascular treatment of these injuries when possible, based on the improved ability to achieve proximal and distal control and manage hemorrhage risk.